The Influence of Repeated Drop Jump Training on Countermovement Jump Performance - Lin He; Yu-Ge Li; Chou Wu; Shun Yao; Yu Su; Guo-Dong Ma; I-Lin Wang (Applied Bionics and Biomechanics)
Countermovement jump (CMJ) is used to assess athletic performance of the lower limbs. Drop jump (DJ) is an effect training method that can improve athlete’s jumping performance. The main purpose of this study is to explore the effects of different drop jump heights (DJH)30, DJH40, and DJH50 cm for 250 drop jumps (DJs250) on CMJ. Eighteen male athletes were selected as subjects. After the 50th, 100th, 150th, 200th, and 250th DJs, perform 5 groups of CMJ (the average of 3 times for each group) and record them as the 50th, 100th, 150th, 200th, and 250th CMJ jumps (CMJs50, CMJs100, CMJs150, CMJs200, and CMJs250). The BTS motion capture system and two force plates are used to record data. The MATLAB software was used to analyze data through one-way ANOVA repeated measures. If there is a significant difference, the LSD method is used for post hoc comparison. Jump height (JH), contact time (CT), reaction intensity index (RSI), average rate of force development (ARFD), left average rate of force development (LARFD), and right average rate of force development (RARFD) of CMJs50, CMJs100, CMJs150, and CMJs200 at DJH50 were greater than those at DJH40 and DJH30 (all p<0.05). DJH50 height and DJs200 training times can improve SSC mechanism and improve athlete CMJ performance.